Profile of Young Adults with Cancer at a University Hospital in Santa Catarina, Brazil. - Sordi, Simone; Rafael Baptistella, Antuani; Locatelli, Claudriana (O Mundo da Saúde, 2020)
Cancer is currently a public health problem, and cancer care is among the most expensive in the social field. To change this scenario, it is essential to carry out studies mainly on the young adult population. This study aimed to describe the clinicalepidemiological and sociodemographic profile of cancer cases in young adults assisted by the public system of a University Hospital. This is a cross-sectional, descriptive study with a quantitative approach carried out at the Oncology Service of Hospital Universitário Santa Terezinha (HUST) – Joaçaba, SC. Data collection was carried out by consulting the medical records of patients aged 20 to 39 years, who were diagnosed with cancer from January 2008 to November 2017. The sample consisted of 502 medical records where the mean age of the individuals was 31.6 years. The main risk factor was the presence of a family history of cancer (55.7%), and surgery (50.2%) was the method of choice for treatment. Of the total, 76.1% were female. However, when assessing the death rate, a greater number was observed in males (19.1%). Tumors of the breast, cervix, thyroid, testis, and colon were the most prevalent. Patients with colon (26.3%) and rectal (42.9%) tumors died more frequently. Such data allowed to characterize the socio-demographic and clinical-epidemiological profile of cancer in the studied region, offering subsidies for the implementation of public policies aimed at improving the support given to the population assisted by the Unified Health System, in the Midwest Region of Santa Catarina.